Cytological Effects of Mutagenic Agents and NaCl on Mitotic Division in Two Iraqi Rice (Oryza sativa L.) Genotypes - Mohammed, Rasha K; Ibrahim, Kadhim M (Al-Nahrain Journal of Science, 2017)
This study was carried out to determine the effects of NaCl (0.00, 50, 100, 150, 180 or 200) mM and two different types of mutagens chemical mutagen ethyl methyl sulphonate (EMS) at 0.5% and physical mutagen UV-B irradiation (40 min time exposure), on mitotic division in two Iraqi rice genotypes Amber 33 (A33) and Amber Baghdad (AB). Different concentrations of NaCl were used. Mitotic index (MI %) was decreased significantly by increasing NaCl concentration, however the highest mitotic index was recorded in mutated genotypes with EMS and UV-B. Different abnormal chromosomes were noticed in mutated plants. Results showed high percentage of abnormal chromosomes in EMS mutated genotypes. In addition no significant differences between genotypes in mean of mitotic index with respect to all experiments.